Personnel management information system in order to create up-to-date and integrated personel data and information in the personnel and Human Resources Agency in Malaka Regency - Kristina Yunita de Rahu; Melkisedek N. B. C. Neolaka; Ajis Salim Adang Djaha (Goodwood Publishing, 2025)
Purpose: This study discusses the personnel management information system in order to create up to date and integrated personnel data and information in the Personnel and Human Resources Development Agency in Malaka Regency. Research Methodology: This study adopted a qualitative approach. Data collection methods for this research will be conducted through interviews, observations, and document searches. The data analysis technique in this study is based on the theory of Miles and Huberman. Results: In the application of the human resources management information system in order to create up-to-date and integrated personel data and information in the Personel and Human Resources Development Agency of Malaka Regency, both input and process are still not good. In addition, there are inhibiting factors for the application of the personnel information system. Conclusions: The absence of SIMPEG hinders efficient personnel administration and prevents the agency from achieving its goal of delivering effective and professional civil service management. Limitations: Researchers find it difficult to make more detailed observations so that they cannot display more related data and information. Contribution: This research can be a scientific basis for evaluating the application of the personnel information system at the Personel and Human Resources Development Agency of Malaka Regency. In addition, this research can be scientific information for students of Public Administration Science.